Microbial and Oligosaccharides Treatments of Feces and Slurry in Reducing Ammonia of the Poultry Farm - Y Yusrizal (Media Peternakan, 2012)
This study was conducted to investigate the effectiveness of Lactobacillus sp and fructooligosaccaride (FOS) to reduce the volatile ammonia formation from chicken excreta and layer slurry. For each treatment-replication, 150 g of fecal material were collected from the poultry farm and placed in 500 ml beaker glass. The fecal sample was then treated with 2% Lactobacillus sp (2.6x106) cfu/g and 2% FOS and covered with plastic wraps. The volatile ammonia contents and pH were measured after one hour of standing (0 d) and repeated at 48 h intervals for 6 d. For the dropping slurry study, 300 g of each layer dropping slurry sample were used. Results indicated that 2% Lactobacillus sp or FOS supplementations in the feces and dropping slurry after 1 h up to 6 d reduced the ammonia odor formation, fecal pH, and moisture content. The Lactobacillus sp and FOS treated manure resulted in increasing  Lactobacillus sp count and reducing in E. coli, Salmonella, and Campylobacter in 6 days for both feces and layer dropping slurry. In addition, reducing moisture content was observed in treated manure. It is concluded that Lactobacillus sp and FOS reduced the volatile ammonia formation and pathogenic bacteria from chicken excreta and layer slurry.